Management extra. Financial management - Elearn; Elearn Limited (Great Britain) (Management extra, 2008)
Stuck for ideas, inspiration or just want to work differently? Management Extra brings all the best management thinking together in one package. The books are practical and well structured to provide an in depth treatment of these management topics. Titles in the series: * Business Environment * Change Management * Development for High Performance * Effective Communications * Financial Management * Information and Knowledge Management
Keywords: Business enterprises : Finance; Industrial management